Incidence and risk factors of nevirapine-associated severe hepatitis among HIV-infected patients with CD4 cell counts less than 250 cells/μL - Weerawat Manosuthi (2018)
Objectives: To determine incidence and risk factors of nevirapine (NVP)-associated severe hepatitis that led to NVP discontinuation among HIV-infected patients with CD4 < 250 cells/μL. Material and Method: A retrospective cohort study was conducted among antiretroviral-naive HIV-infected patients who had baseline CD4 < 250 cells/μL and were initiated NVP-based antiretroviral therapy (ART) between January 2003 and October 2005. All patients were categorized to group A: occurred clinical hepatitis and group B: did not occur clinical hepatitis. All were followed until 6 months after ART. Results: There were 910 patients with a mean age of 35.4 years, 57% were males and median (IQR) CD4 cell count was 27 (9-80) cells/μL; contributing 5,006 person-months of observations. Ten (1.1%) patients were in group A and 900 (98.9%) patients were in group B. Incidence of clinical hepatitis was 2 per 1,000 personmonths. Probabilities of clinical hepatitis at 0.5, 1, 2, 3 and 6 months after ART were 0.2%, 0.5%, 0.7%, 0.8% and 1.1%, respectively. By Cox regression analysis, baseline AST ≥ 1.5 times of upper limit was associated with higher incidence of clinical hepatitis (p = 0.019, HR = 5.83, 95% CI = 1.33-25.51). Conclusion: Incidence of NVP-associated severe hepatitis that lead to NVP discontinuation among HIV-infected patients with baseline CD4 < 250 cells/μL is low. The higher baseline AST is also associated with a higher risk of severe hepatitis.